Reconstruction of Ship Propeller Wake Field Based on Physics-Informed Neural Networks - HOU Xianrui, ZHOU Xingyu, HUANG Xiaocheng (Shanghai Jiaotong Daxue xuebao)
Physics-informed neural networks (PINN) are applied to the reconstruction of the ship propeller wake field. First, the principle and basic framework of PINN were introduced. Then, the Burgers equation was selected to verify the feasibility of PINN in solving partial differential equations. After that, the propeller of KVLCC2 in open water is simulated using computational fluid dynamics (CFD) software STAR CCM+, and the flow field information of the KVLCC2 propeller is obtained. Based on the simulated flow field information data, the training sample set was constructed to train PINN. The trained PINN was used to infer the approximate solution of the governing equation at any time and space. Finally, the velocity and pressure distribution obtained by PINN were compared with the velocity and pressure distribution simulated by STAR CCM+. The results validate the reliability of PINN in propeller wake field reconstruction, which can be concluded that PINN can be applied to the reconstruction of the ship propeller wake field.